2021
DOI: 10.48550/arxiv.2104.03317
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Binary-Stripped Stars as Core-Collapse Supernovae Progenitors

David Vartanyan,
Eva Laplace,
Mathieu Renzo
et al.

Abstract: Most massive stars experience binary interactions in their lifetimes that can alter both the surface and core structure of the stripped star with significant effects on their ultimate fate as core-collapse supernovae. However, core-collapse supernovae simulations to date have focused almost exclusively on the evolution of single stars. We present a systematic simulation study of single and binarystripped stars with the same initial mass as candidates for core-collapse supernovae (11 − 21 M ). Generally, we fin… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 71 publications
0
7
0
Order By: Relevance
“…This is due to the extra mass loss binaries undergo, lowering the final helium core masses. Thus for a given helium core mass at core-collapse binary-stripped systems have a higher initial mass (Kippenhahn & Weigert 1967;Habets 1986), expanding the range in initial masses over which we assume a successful explosion occurs (Vartanyan et al 2021). For our systems, a cut of M He,final < 7 M is equivalent to a cut of M init < 19 M for single stars and M init < 22 M for binaries.…”
Section: Bh Formation Assumptionmentioning
confidence: 85%
“…This is due to the extra mass loss binaries undergo, lowering the final helium core masses. Thus for a given helium core mass at core-collapse binary-stripped systems have a higher initial mass (Kippenhahn & Weigert 1967;Habets 1986), expanding the range in initial masses over which we assume a successful explosion occurs (Vartanyan et al 2021). For our systems, a cut of M He,final < 7 M is equivalent to a cut of M init < 19 M for single stars and M init < 22 M for binaries.…”
Section: Bh Formation Assumptionmentioning
confidence: 85%
“…Previous studies have shown that the suggested explodability metrics depend on metallicity and rotation (O'Connor & Ott 2011), the adopted stellar wind mass-loss rates (even if these only act early during a star's evolution, Renzo et al 2017), overshooting (Davis et al 2019), and occurrence of convective shell mergers (e.g., Vartanyan et al 2021). Other parameters might play a significant role in shaping the density structure of the core at the onset of core collapse.…”
Section: Conclusion and Discussionmentioning
confidence: 98%
“…This is unfeasible for now as the computational expense is quite large. Recent studies of the single and binary progenitors of core-collapse supernovae evolved all the way to core-collapse explore tens to hundreds of stars (e.g., Sukhbold et al 2016;Vartanyan et al 2021). Doing this for millions of stars is unrealistic.…”
Section: Discussionmentioning
confidence: 99%